Nilai-Nilai Pendidikan Islam dalam Pelaksanaan Aqiqah - Nur Aidila Fitria; Rizal Awaludin; Sa’baniah; Laila; Muhammad Yasin (PT. Penerbit Tiga Mutiara, 2024)
The values of Islamic education are benchmarks of behavior that are in line with Islamic teachings and must be upheld in both the private and public spheres. One of the means that parents can do in providing Islamic education to their children is by carrying out aqiqah. This study aims to analyze the values of Islamic education contained in the implementation of aqiqah. This research uses a literature study research methodology or library research, which is the process of collecting materials related to research from books, journals, literature, and other publications that deserve to be used as sources for further research by the author. As a result, there are five points of Islamic education in the implementation of aqiqah, namely the value of faith education which shows that aqiqah as a form of obedience in religion, the value of worship education which shows that aqiqah as a form of self-sacrifice to Allah, the value of moral education which shows that aqiqah as an effort to form morality, the value of social education which shows that aqiqah can strengthen the bonds of friendship, and the value of health education which shows that aqiqah is carried out by slaughtering healthy animals and not defective, and halal for consumption. In addition, there are three additional educational values in the implementation of aqiqah, namely giving a name to the child as a prayer and his identity, shaving the hair as a form of obedience and preventing disease and fostering an attitude of charity, and men-tahnik or giving something sweet to the baby's mouth as an effort so that one day the child has a good speech in speaking.